2021
DOI: 10.1038/s41563-021-01119-8
|View full text |Cite
|
Sign up to set email alerts
|

Interface polarization in heterovalent core–shell nanocrystals

Abstract: The potential profile and the energy level offset of core/shell heterostructured nanocrystals (h-NCs) determine the photophysical properties and the charge transport characteristics of h-NC solids. However, limited material choices for heavy metal-free III-V/II-VI h-NCs pose challenges in comprehensive control of the potential profile. Herein, we present an unprecedented approach to such control by steering dipole moments at the interface of III-V/II-VI h-NCs. The controllable heterovalency at the interface is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 45 publications
(37 reference statements)
3
65
0
Order By: Relevance
“…[ 33 ] The red – and green‐emitting InP/ZnSe/ZnS QDs were prepared as described by Hahm et al. [ 34,35 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 33 ] The red – and green‐emitting InP/ZnSe/ZnS QDs were prepared as described by Hahm et al. [ 34,35 ]…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Bae et al. [ 50 ] reported that the interface polarization produced by III–VI bond, would increase the optical bandgap but without detailed element analysis, which might be part of the origin for the blue‐shift of the emission wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…These two results confirm the fact that much anion exchange results in the smaller size of InP core, therefore the blue-shift of emission wavelength under I − -rich environment. In addition, Bae et al [50] reported that the interface polarization produced by III-VI bond, would increase the optical bandgap but without detailed element analysis, which might be part of the origin for the blue-shift of the emission wavelength.…”
Section: H Nuclear Magnetic Resonance (Nmr) Measurements Tomentioning
confidence: 99%
“…Core-shell nanoparticles (CS-NPs) are attracting significant interest in chemistry and material science, and are widely used in many applications such as catalysis, optics, electronics, and biomedical applications due to their novel optical, magnetic and electronic characteristics [1][2][3][4][5][6] . The unique and versatile functionalities of CS-NPs arise from the physical and chemical properties of both the core and the shell 7,8 , determined by the three-dimensional (3D) arrangement of the atoms, particularly at the core-shell interfaces.…”
Section: Introductionmentioning
confidence: 99%